(untitled) (Journal of Advanced Mining Modeling, 2026)
The investigation into noise pollution at the La Encantadora S.A. quarry aimed to evaluate the noise levels generated by limestone drilling and its impact on occupational and environmental health. A descriptive-correlational design was used, with on-site measurements at 29 points and surveys of 462 workers, complemented by statistical analyses (Student’s t-test, Spearman’s rank correlation coefficient, and Cronbach’s alpha reliability coefficient). The results showed noise levels between 50.9 and 74.3 dB, exceeding the WHO’s recommended limit (70 dB), although within national legal parameters (80–85 dB). The average was 60.22 dB, reflecting moderate exposure, but with critical areas along roads and in extraction zones. 85.1% of the workers perceived high levels of noise pollution, which correlated significantly with the intensity of the drilling, confirming risks of auditory fatigue, stress, and hearing loss. These findings highlight the urgent need to implement hearing conservation programs, acoustic barriers, continuous environmental monitoring, and preventative training. In short, noise management in non-metallic mining is not only a regulatory obligation but also an ethical commitment to health, human dignity, and environmental sustainability References [1] González, A., Pérez, B., & Rodríguez, S. (2023). Pequeña minería no metálica y su impacto en el desarrollo económico y social. Revista Latinoamericana de Minería, 41(1), 22-40. https://doi.org/10.15381/iigeo.v26i51.25261 [2] Martínez, F., & López, G. (2022). Contaminación acústica en minería y su impacto en comunidades cercanas. Estudios Ambientales, 26(3), 67-85. [3] Fernández, J., López, M., & Torres, R. (2021). Impacto del ruido en la salud ocupacional de trabajadores mineros. Revista de Ingeniería Ambiental, 35(2), 45-60. https://repositorio.upch.edu.pe/bitstream/handle/20.500.12866/16904/Ruido VergaraGalvez_Jose.pdf?sequence=1&isAllowed=y [4] Rodríguez, S., & Pérez, L. (2024). Calidad de vida y exposición al ruido en zonas mineras. Estudios Sociológicos Mineros, 21(4), 88-105. https://tesla.puertomaderoeditorial.com.ar/index.php/tesla/article/view/251 [5] López, R., Sánchez, M., & Vega, J. (2023). Criterios de control acústico en perforación de piedra caliza. Ingeniería Minera Aplicada, 30(5), 98-115. [6] García, P., & Torres, L. (2022). Eficiencia operativa y costos asociados a la contaminación acústica en minería no metálica. Estudios Mineros, 28(4), 112-130. https://doi.org/10.55204/trc.v3i2.e251 [7] Ramírez, H., & Pérez, C. (2024). Protección de la salud ocupacional en minería no metálica. Revista de Seguridad Minera, 12(1), 33-50. [8] Hernández, V., & Castro, E. (2023). Interacción entre contaminación acústica y perforación en minería sostenible. Ciencia y Tecnología Minera, 15(2), 55-72. https://doi.org/10.15381/iigeo.v26i51.25261 [9] Ministerio de Energía y Minas. (2023). Normativas sobre contaminación acústica en actividades extractivas. Lima, Perú. [10] Gómez, C., Ramírez, D., & Mendoza, F. (2022). Relación entre niveles de ruido y productividad en canteras de piedra caliza. Minería y Medio Ambiente, 19(3), 78-95. [11] Ruiz, M., & Mendoza, T. (2023). Factores que influyen en la contaminación acústica en minería no metálica. Ingeniería Geológica y Minera, 17(2), 44-62. [12] Sánchez, J., Morales, P., & Vega, R. (2024). Evaluación del grado de contaminación acústica en perforación minera. Ciencia y Tecnología Extractiva, 11(3), 71-90. [13] Vega, R., & Morales, P. (2023). Indicadores de eficiencia en perforación de piedra caliza. Estudios Técnicos Mineros, 14(2), 56-74. [14] Serna Sánchez, J. (2018). Metodología de la investigación científica. Editorial Universitaria. [15] Paredes, J., Vargas, M., & Sandoval, C. (2023). Diseño experimental en estudios de contaminación acústica en minería. Minería y Medio Ambiente, 19(3), 78-95. [16] Fuentes, R., & Morales, P. (2023). Estrategias de muestreo en estudios de impacto ambiental en minería no metálica. Estudios Geológicos y Mineros, 21(3), 78-95.